Integrity Assessment of Dented Aboveground Steel Storage Tank After Hydrostatic Testing - Wira Herucakra; Luh Putri Adnyani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This paper presents a comprehensive structural integrity assessment of a 50,000-kiloliter aboveground steel storage tank that experienced shell denting during hydrostatic testing. Dents and geometric imperfections are known to significantly affect the buckling behavior and load-bearing capacity of storage tanks. To evaluate the tank’s fitness for service (FFS), a Level 3 assessment was conducted following API 579-1/ASME FFS-1 Part 8 standards. Finite element analysis was employed to simulate the elastic stress distribution and fatigue behavior under various loading conditions, including hydrostatic pressure, wind, and seismic loads. Results revealed that shell course 7 and 8 experienced stress increases of up to 2282% compared to the undistorted condition, with von Mises stress remaining below the allowable limits. A fatigue analysis confirmed that stress amplitudes were below the fatigue threshold, resulting in infinite fatigue life. Furthermore, discharge simulation indicated that improper dewatering could induce external pressure exceeding the material’s yield strength, leading to localized plastic deformation. Nevertheless, the dented tank was found to be structurally sound and compliant with API 650 and API 579-1/ASME FFS-1 criteria. The study highlights the importance of proper discharge procedures and confirms that no immediate repair is required for continued safe operation of the tank.